Предмет: Математика,
автор: MrKwippi
решите(-x-6x)+(-4-6)=-9
Ответы
Автор ответа:
0
(-x - 6x) + (-4 - 6) = -9
-7x - 10 = -9
7x + 10 = 9
7x = -1
x =
-7x - 10 = -9
7x + 10 = 9
7x = -1
x =
Автор ответа:
0
(- х - 6х) + (- 4 - 6) = - 9
(- 7х) + (- 10) = - 9
- 7х - 10 = - 9
- 7х = - 9 + 10
- 7х = 1
х = - 1/7
Ответ: х = - 1/7.
(- 7х) + (- 10) = - 9
- 7х - 10 = - 9
- 7х = - 9 + 10
- 7х = 1
х = - 1/7
Ответ: х = - 1/7.
Похожие вопросы
Предмет: Алгебра,
автор: al041
Предмет: Обществознание,
автор: darkangel2020
Предмет: Алгебра,
автор: al041
Предмет: Алгебра,
автор: Nastenka7777777